The Determinants of Startup Risk in Indonesia: A Bibliometrical Analysis - Zulfikar , Ian; Digdowiseiso , Kumba (CV ODIS, 2023)
This research presents a bibliometric analysis of startup risk in Indonesia based on scientific publications from 2015 to 2023. Data was obtained from Google Scholar with the keyword